Starry River of the Sky - Lin, Grace (New York : Little, Brown, 2012)
An innkeeper's chore boy discovers that a visitor's stories hold the key to returning the moon to the Starry River of the Sky.
Companion book to: Where the mountain meets the moon.
Includes bibliographical references.
Keywords: Fairy tales; Moon -- Fiction; Storytelling -- Fiction; Fairy tales; Moon -- Juvenile fiction; Storytelling -- Juvenile fiction